Elisabetta Bianco, Sparta e i suoi navarchi , Edizioni dell’Orso (“Fonti e studi di storia antica” 21), Alessandria 2018, pp. VI + 186, ISBN 978-88-6274850-6 - Masone, Leonardo (ΠΗΓΗ/FONS, 2020)
Book review